Arabic Language Rules in Forming a Scholarly Personality of Exegete: Language Acquisition - Hasballah Thaib, Zamakhsyari; Mohd. Shamsuddin, Salahuddin (Al-Ḍād Journal, 2023)
None of the scholars of the Qur’an who set the conditions that must be fulfilled by an exegete disagreed that Arabic language is one of the components of the exegete. However, their opinions differed regarding the required level of knowledge of Arabic language that the exegete should have. This research demonstrates the required level of knowledge of Arabic language, based on what scholars wrote about the origins of interpretation through induction. The research reached the most significant results as follows: (1) The scholars unanimously agreed that knowledge of the Arabic language is an essential component of the exegete, and his interpretation of the Qur’an is not valid without it, and his opinion is not accepted without it, (2) The differences in the opinions of scholars regarding the level of knowledge of Arabic language that should be obtained by the exegete and the degree which he must reach it, (3) The multiplicity of opinions of scholars in considering the Arabic sciences that the exegete should know, (4) It has been proven that the issues of the principles of interpretation that the exegete must practice in his interpretation of the Qur’an are issues related to the grammar, morphology, rhetoric, language, and logic. Keywords: rules of Arabic language, Arabic linguistics sciences, forming the exegete, conditions of the exegete, understanding the Qur’an